Evaluating gender representation in Business Studies curriculum and pedagogy: a case study of Independent schools of the Gauteng province in South Africa - Morgan, Luciel Venesa (Stellenbosch : Stellenbosch University, 2026)
Thesis (MEd)--Stellenbosch University, 2025.